IDENTIFIKASI KECAKAPAN MATEMATIS KONTEKS BUDAYA BANTEN PADA MAHASISWA DI UNIVERSITAS SULTAN AGENG TIRTAYASA - Etika Khaerunnisa; Novaliyosi Novaliyosi (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
Mathematical skills are needed as a requirement for progress in modern times, and as a provision for the competitive 21st century. This puts pressure on students needing mathematical skills as a result of the learning process. Given the mathematics education students will be a professional teacher who is required to identify and improve the mathematical skills of students in school. So it is necessary to be anticipated early on for prospective math teacher who later become a teacher by knowing the level of his mathematical skills, based on the description of the students can do self-evaluation and follow-up on the advantages and weaknesses in each aspect of mathematical skill that includes comprehension concept, procedural fluency, strategic competence, and adaptive reasoning. The cultural context is integrated so that prospective teachers are able to see the mathematical aspects of their local culture and make it easier to solve the mathematical problems given through the Banten cultural context. The study purposes is to know and describe the picture of mathematical skills in the context of Banten culture in prospective math teachers. The research methode is qualitative method. The research instrument consists of a matter of mathematical skills test of Banten cultural context and interview guidance. Subjects in this study were students of Mathematics Education Department semester I academic year 2017/2018 of 113 students. The results showed that 1) Overall mathematical skill of cultural context of Banten mathematics teacher candidate of University of Sultan Ageng Tirtayasa including medium categorical; 2) There are 50% of mathematics teacher candidates possessing a mathematical skill in the Banten cultural context in the high category, and 30% of math candidates have moderate mathematical skills, and 20% of teachers have low mathematical skills in Banten cultural context; 3) The average aspect of mathematical skill of the Banten cultural context is highest in conceptual concept of understanding, while the average in the aspect of the lowest mathematical skill is on the aspect of the ability of adaptive reasoning. Keywords: Mathematical Skill, Banten Culture Context